Does Visual Merchandising Influence on Consumer Purchasing Intention in the Fashion Retail Stores? The Mediation Role of Consumer Perception - H A Murad, Zainab; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
The main aspiration of this study is to figure out the visual merchandising elements which influence on an individual’s purchase intention. A sample of 302 respondents available at different fashion stores in Kuwait City was used to get the study outcomes following the quantitative analysis. The Smart PLS 3.0 was used for analyzing the data. This study claims that there is a positive and significant relationship between store layout and consumer purchasing intention. Then, a positive and significant relationship is also found between product display and consumer purchasing intention. After that, a positive and significant relationship is found as well between music and consumer purchasing intention. Furthermore, a positive and significant relationship is found between color & lighting and consumer purchasing intention. Moreover, a positive and significant relationship found between cleanliness and consumer purchasing intention. This study also reveals that consumer perception mediates the relationship between product display, music, color & lighting and cleanliness with consumer purchasing intention. This study claims that consumer perception does not mediate the relationship between store layout and consumer purchasing intention. The outcomes of this study will help the policy makers, government and entrepreneurs to make their fashion stores gorgeous.